Comparative Profitability of the Modern and Traditional Variety of T. Aman Rice in Mymensingh District of Bangladesh - Zaman, Md Rifatuz; Aker, Tanjima; Nishat, Nazneen Islam (International Journal of Sustainable Agricultural Research, 2022)
This study was conducted to identify the socioeconomic characteristics of Transplant Aman (T. Aman) rice producers, compare the profitability of modern and traditional varieties and, analyze the factors affecting the production of modern and traditional T. Aman rice varieties. The multistage sampling procedure was used for selecting 60 farmers from Muktagacha, Ishworgonj and, Fulbaria Upazila under the Mymensingh district of Bangladesh. A semi-structured interview schedule was used for the purpose of collecting primary data. Tabular analysis, undiscounted BCR and, Cobb-Douglas production model were used for analyzing the data. The major findings of the study were that about 43.34% of the respondents belonged to the age between 46-65 years, 71.67% were male, 41.67% had primary education only, agriculture was the main occupation of 75% of the respondents and 53.33% had access to credit. The per acre average net return was Tk 16760.71 with a BCR of 1.47. The comparative analysis revealed that the per acre average net return and BCR of modern variety of T. Aman were Tk 23737.98 and 1.68 and of traditional variety of T. Aman were Tk 10601.58 and 1.27, respectively. The results of Cobb-Douglas production model showed that human labor cost, Urea cost, Boron cost, seed cost, pesticides cost, threshing and, drying cost had significant effects on the production of the modern variety. The findings of this study suggest that the production of the modern variety of T. Aman will be profitable which in turn will contribute to ensuring food security among the rural poor.